1971
DOI: 10.1038/230434a0
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron Radiation as a Source for X-ray Diffraction

Abstract: Some preliminary results have been obtained with synchrotron radiation from the 7.5 GeV electron synchrotron Deutsches Elektronen - Synchrotron (DESY) in Hamburg as a source for X-ray diffraction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0
1

Year Published

1975
1975
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(81 citation statements)
references
References 9 publications
0
80
0
1
Order By: Relevance
“…The evidence for DESY is that H=8 mm and W=4 mm. (Rosenbaum, Holmes & Witz, 1971;Tuomi, Naukkarinen, Laurila & Rabe, 1973;Tuomi, Naukkarinen & Rabe, 1974), while for NINA H=0.5 mm (Beaumont & Hart, 1974) and the present work shows that W=0.5 ram. Unlike conventional X-ray diffraction topography with characteristic radiation, the whole source contributes to the intensity diffracted by each point in the sample.…”
Section: Resolutionmentioning
confidence: 75%
See 1 more Smart Citation
“…The evidence for DESY is that H=8 mm and W=4 mm. (Rosenbaum, Holmes & Witz, 1971;Tuomi, Naukkarinen, Laurila & Rabe, 1973;Tuomi, Naukkarinen & Rabe, 1974), while for NINA H=0.5 mm (Beaumont & Hart, 1974) and the present work shows that W=0.5 ram. Unlike conventional X-ray diffraction topography with characteristic radiation, the whole source contributes to the intensity diffracted by each point in the sample.…”
Section: Resolutionmentioning
confidence: 75%
“…Because of betatron oscillations about the stable orbit the effective source size is larger than one might expect. For the X-ray region of the spectrum the effective source size is about 0.5 mm square for NINA (Beaumont & Hart, 1974) and 4 mm by 8 mm for DESY (Rosenbaum, Holmes & Witz, 1971). The effective source size from SPEAR should be less than either of these.…”
Section: The Source Characteristicsmentioning
confidence: 99%
“…It is 40 y since the first synchrotron diffraction from insect muscle was recorded (13). Thanks to that pioneering work and subsequent improvements in synchrotron and X-ray detector technology, we were able to record real-time X-ray diffraction movies of stretch activation.…”
mentioning
confidence: 89%
“…In 1970, the first experimental use of SR in biology was made by Rosenbaum, Witz and Holmes at the Deutsches Elektronen Synchrotron (DESY), Hamburg, Germany, where it was shown that diffraction from a muscle fibre could be recorded with very much shorter exposure times than with a laboratory-based X-ray source (Rosenbaum et al 1971). From that time, the special brightness of SR began to be appreciated for MX.…”
Section: Introduction-early Historymentioning
confidence: 99%